Combined effects of reflexology massage and respiratory relaxation on pain following chest tube removal in heart surgery patients - Zainab Bahramian; Majid Kazemi; Reza Vazirinejad; Hadi Hasani (Journal of Cardiothoracic Surgery)
Abstract Background and aim Removing the chest tube in cardiac patients after surgery is one of the worst experiences of hospitalization in the intensive care units. Various pharmacological and non-pharmacological methods are available to control pain in these patients. This study aimed to investigate the combined effect of reflexology massage and respiratory relaxation on pain following chest tube removal in cardiac surgery patients of Shahid Beheshti Hospital in Shiraz, Iran, in 2023. Methods This was a double-blind randomized clinical trial performed on 140 patients who underwent heart surgery and had a chest tube in Shiraz, Iran. The samples were randomly divided into four groups: 1- control group, 2- respiratory relaxation group, 3- foot reflex massage group, and 4- a combination of respiratory relaxation and reflexology massage. To collect data, two demographic questionnaires, and a visual analog scale were used. Results The participants of the four groups were not meaningfully different in terms of age, BMI, duration of surgical operation, gender, job, education, place of residency, number of chest tubes, history of operation (P = 0.99, 0.31, 0.06, 0.81, 0.97, 0.96, 0.17, 0.10, 0.89 respectively). The mean scores of pain intensity during chest tube removal, and 15 min after chest tube removal were not statistically different among the four groups of study (P = 0.15, 0.54 respectively); However, just after chest tube removal, the mean scores of pain intensity differed meaningfully among four groups (P = 0.008). Conclusion The results showed that reflexology massage and respiratory relaxation both reduce pain immediately after chest tube removal in heart surgery patients. Also, the combination of these two techniques was more effective in reducing patients’ average pain.